Особенности гранитоидного магматизма в Гуляйпольской гранит-зеленокаменной структуре (Приазовский мегаблок УЩ) - Артеменко, Г.В.; Самборская, И.А.; Швайка, И.А.; Калинин, В.И. (Мінералогічний журнал, 2010)
Изменения химического состава гранитоидов на Гуляйпольском блоке от архейских (3,1) к протерозойским
(2,1 млрд лет) выражаются в возрастании содержания литофильных (K, Rb, Ba) и высокозарядных (Nb, Y, Th)
элементов, повышении значений Rb/Sr и Nb/Ta отношений, что отражает степень кратонизации континентальной коры. Гранитоиды тоналит-трондьемит-гранодиоритовой формации выплавлялись, вероятно, в результате
частичного плавления метабазитов зеленокаменных поясов в процессе субдукции. Гранитоиды шевченковского
(2,835 ± 0,03), ремовского (2,97 ± 0,18), добропольского (2,1 ± 0,015 млрд лет) комплексов имеют "смешанные"
геохимические характеристики мантийных и коровых гранитов, что характерно для коллизионной геодинамической обстановки. Двуполевошпатовые постколлизионные граниты анадольского комплекса имеют геохимические характеристики коровых гранитов и по составу соответствуют внутриплитным гранитам. Еволюційні зміни хімічного складу гранітоїдів на Гуляйпольському блоці від архейських (3,1) до протерозойських (2,1 млрд рр.) проявились у зростанні вмісту літофільних (K, Rb, Ba) і високозарядних (Nb, Y, Th)
елементів, підвищенні значень Rb/Sr і Nb/Ta співвідношень, що відображає ступінь кратонізації континентальної кори. Гранітоїди тоналіт-тронд’єміт-гранодіоритової формації виплавлені, ймовірно, у результаті часткового
плавлення метабазитів зеленокам’яних поясів у процесі субдукції. Гранітоїди шевченківського (2,835 ± 0,03),
ремівського (2,97 ± 0,18), добропільського (2,1 ± 0,015 млрд рр.) комплексів мають "змішані" геохімічні характеристики мантійних і корових гранітів, що є характерним для зон колізії. Двопольовошпатові постколізійні граніти анадольського комплексу мають геохімічні характеристики корових гранітів та за складом відповідають
внутрішньоплитним гранітам. Under the new geological data, the granite-greenstone association of the Gulyaipole block (3.2—2.92 Ga)
was formed on Paleoarchean granulitic-gneiss crust as a result of lifting the Mesoarchean mantle plume. The plume
activity is connected with the emergence of granitoid intrusions of Mesoarchean tonalite-trondhjemite-granodiorite
(TTG) formation and probably Shevchenko granodiorite complex. Early intrusions of tonalites and granodiorites of TTG
formation were formed in the interval of 3.1—3.0 Ga; trondhjemites of TTG formations and granites of Remov complex
on Volchansk and Remov granulite-gneiss blocks — 2.92—2.97 Ga; the introduction of intrusives granodiorite of the
Shenchenko complex ― 2.835 Ga; collision of Gulyaipole granite-greenstone block enclosing Volchansk and Remov
granulite-gneiss blocks — 2.10 ± 0.015 Ga; the introduction of granites of Dobropol’e and Anadol complexes (2.1 Ga).
Evolutionary changes in the chemical composition of granitoids in Gulyaipole block from Archean (3.1 Ga) to the
Proterozoic (2.1 Ga) — are expressed in an increase in the contents of lithophile (K, Rb, Ba) and highly charged (Nb, Ya,
Th) elements increasing Rb/Sr and Nb/Ta relations, which reflects the degree of kratonization of the continental crust.
TTG formations granitoids were probably produced as a result of partial melting of metabasites of greenstone belts in the
process of subduction. The granitoids of the Shevchenko (2.835 ± 0.03 Ga), Remov (2.97 ± 0.18 Ga), Dobropolie (2.1 ±
± 0.015 Ga) complexes have "mixed" geochemical characteristics of the mantle and crystal granites, that is typical of the
collisional geodynamic environment. Two feldspare, postcollision granites of the Anadol complex have geochemical
characteristics of crustal granites and as to their composition correspond to intraplate granites.